Scientific Collaborations: How do we Measure the Return on Relationships? - Jeanne Marie Fair; Martha Mangum Stokes; Deanna ePennington; Ian eMendenhall (Frontiers Media S.A., 2016)
Emerging infectious diseases (EIDs) are a challenge for public health and biosurveillance infrastructure across the globe. These etiological agents, which cause EIDs, are primarily of zoonotic origin. Due to the complexity of zoonotic pathogens, research and response to EIDs must be a transdisciplinary effort. While crisis and circumstance may be the catalyst for responding to an outbreak, we can use the example of how transdisciplinary scientific collectives can be organized more in advance of crises, and therefore become transformative and perhaps even avert crisis (Pennington et al., 2013). Leading indicators that a cooperative engagement is producing value and is sustainable are based on the ideas of return of investment and do not regard the inherent importance of relationships. In this article, we apply the idea of return of relationships (ROR) and propose a method for measuring the return of relationships, using a systems dynamics modeling framework commonly used in epidemiology. Using the scientific collaboration that emerged from the Hanta Virus outbreak of 1993 in North America and a training workshop for biosurveillance of bats held in Singapore in 2014, we apply a methodology for visualizing and measuring the relationship networks and outcomes.